Resolution of Environmental Crimes by the Dayak Ngaju Indigenous Community through the Huma Betang Principle - Nuredy Irwansyah Putra; Marcus Priyo Gunarto (IJCLS (Indonesian Journal of Criminal Law Studies), 2026)
This study examines the mechanisms for resolving environmental crimes practiced by the Dayak Ngaju indigenous community in Central Kalimantan, focusing on the Huma Betang principle as the foundation of their social and ecological values. Using a normative legal approach and the theoretical frameworks of De Voy and Leopold Pospíšil, the research reveals that Dayak Ngaju customary law is not only socially legitimate but also represents a form of living law that effectively maintains environmental balance and resolves conflicts through collective consensus. The Huma Betang principle, emphasizing communal solidarity, harmony with nature, and deliberation-based decision-making, serves as the cornerstone for both the imposition of sanctions and ecological restoration. The findings underscore the importance of recognizing customary law within the framework of legal pluralism and highlight the need to integrate indigenous legal systems into the national legal order to strengthen ecological justice and enhance the effectiveness of environmental law enforcement.